Legal and Taxation essentials for business startups - Mundra, Raghav (ATLAS SkillTech University, 2024)
In this black book, we will explore the key components that every entrepreneur should be aware of before starting on their business journey. From choosing the right business structure to fulfilling tax obligations, this guide will equip readers with the knowledge needed to make informed decisions and avoid potential challenges.
Project Report on Legal and Taxation essentials for business startups (2022-24) Under the Guidance of Prof. Chetana Asbe
Keywords: knowledge; business